Teachers' Efforts to Educate Positive Student Behavior Through Strengthening Religious Values, Practices and Role Models - Budiman, Fajar; Mega, Enni; Taufik Hidayat (Al-Kahfi: Jurnal Pendidikan Agama Islam, 2025)
Educational problems such as deviant behavior are still often found in schools among students. This reality is considered by some groups to be a form of school failure in fostering its students, and it is a challenge for school management elements, especially Islamic religious education teachers. The purpose of this study is to determine how Islamic religious education teachers educate students through academic activities and extracurricular activities at school. This study uses a qualitative method with a case study approach. Data sources were taken from the principal and 5 Islamic religious education teachers, and 5 students were conducted through in-depth interviews selected using purposive sampling techniques, while the selected informants have met four criteria, namely understanding the problems being studied well, still active in the field being studied, having time to provide information to researchers, and providing information in accordance with the facts that occur in the field. After the interviews were completed with all informants, a transcription process was carried out, then the author took themes that were appropriate to the research needs and the data were analyzed using interactive techniques miles and huberman. The results of the study show that the efforts of Islamic religious education teachers in educating positive student behavior: (1) teaching the values ​​of faith in learning activities. (2) practicing worship activities in learning such as praying before and after learning, carrying out Al-Quran recitation activities before learning begins. (3) providing examples and role models in behaving at school. The findings of this study can be input for teachers in educating students about positive behavior through academic and extracurricular activities.